Synergistic combination of PMBA and 5-fluorouracil (5-FU) in targeting mutant KRAS in 2D and 3D colorectal cancer cells. Issue 4 (April 2022) - Qayum, Arem; Magotra, Asmita; Shah, Syed Mohmad; Nandi, Utpal; Sharma, P.R.; Shah, Bhahwal Ali; Singh, Shashank Kumar
Abstract: β-Boswellic acid (β-BA), a potent NF-kB signaling pathway inhibitor, has shown synergistic anti-cancerous activity (NCT03149081, NCT00243022 and NCT02977936) in various clinical trials as complementary therapies. The study has been conducted to investigate the effect and efficacy of 2-pyridin-4-yl methylene β-boswellic acid (PMBA) and 5-Flourouracil (5-FU) in combination therapy for the treatment of KRAS mutant colon cancer. Analysis of isobologram showed synergistic combination index (CI > 1) of PMBA and 5-FU against the HCT-116 G13D and SW-620 G12V cell lines. The growth-inhibiting PMBA also caused apoptosis mediating effects with dose-dependent increase in caspase-3 activity, while inhibiting the formation of colonies in combination with 5-FU. As evident, PMBA affected colorectal 3D CSC properties including the ability to self-renew along with the expression of multi-drug resistance genes, viz ., ABCB1, ABCC1 and ALDH1A1, ALDH1A2, ALDH1A3, ALDH3A1, and CSC markers like CD44, CD166, EPCAM, OCT-4, SOX-2, and NANOG compared with those in 2D model explaining the expression pattern of oncogenic KRAS G13D, G12V mutation. When examined for plasma level of PMBA (20 mg) and PMBA+5-FU (20 + 40 mg), a time-dependent increase in the level of the drug (5-FU) was detected, indicating its absorption and bioavailability with excellent half-life of the PMBA for both routes of administration (IV and Oral), thereby indicating a new adjuvant therapy for KRAS mutant colon cancer. Graphical abstract: Image 1 Abstract : Colon cancer, PMBA, 5-fluorouracil, KRAS, Spheroid-formation (Colonospheres), Combination study, Pharmacokinetics.